Performance analysis of three-phase induction motor for railway propulsion system - Syamsul Kamar; Meiyanne Lestari; Respatya Teguh Soewono; Sofwan Hidayat; Hilda Luthfiyah; Okghi Adam Qowiy; Fauzi Dwi Setiawan; Mulyadi Sinung Harjono (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A three-phase induction motor absorbs the most electric power among other electrical loads. Therefore, three-phase induction motors are the primary electric motors used in industrial applications thanks to their simple construction and easy operation, as well as low cost and low maintenance costs. Efficiency is a critical parameter that characterizes an induction motor as a traction motor. The traction motor is defined as the engine's effectiveness in converting electrical power at its input into mechanical energy by rotating torque on its axis. One way to analyze the efficiency is to use test data obtained from laboratory tests in case-loaded and no-load tests. Calculations using several formulas on the efficiency of an induction motor as a traction motor produce the same result, namely the efficiency of 98.6% by applying variable frequency drive (VFD). The result of laboratory tests and their analysis can be used as a reference for designing three-phase induction motors for railway traction motors, especially traction motors for high-speed trains.